Video Cultures
VII, 241 p. 5 illus.
Keywords: Over the past decade, there has been a huge increase in ordinary people's access to video production technology. These essays explore the theoretical significance of this trend and its impact on society, as well as examining a wide range of case studies, from camcorders and camera phones to YouTube and citizen journalism.